Filsafat Pendidikan Islam dan Transformasi Pendidikan Pesantren di Era Modern - Dwi Indah Saputri; Syifa Husniya Barokah; Tuwasih Setianingsih (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This study discusses the role of Islamic educational philosophy in guiding the transformation of pesantren education in the modern era. Islamic education in Indonesia plays an important role in shaping students’ character, spirituality, and intellectual abilities, with pesantren as one of the oldest institutions that preserve Islamic values. However, the rapid development of globalization and technology requires pesantren to adapt without losing their identity. This research aims to explain how Islamic educational philosophy becomes the foundation for transformation and to identify forms of change that are relevant to current challenges. The study uses a qualitative approach through a literature review, collecting data from journals and other relevant sources. Data are analyzed using content analysis by organizing and comparing findings from different studies. The results show that pesantren transformation occurs through a selective adaptation process, combining traditional values such as moral education, spirituality, and classical learning with modern elements like curriculum integration, interactive learning methods, and digital technology. Some challenges still exist, including limited facilities, unequal access to technology, and the need to improve teacher competence. Islamic educational philosophy helps maintain balance between intellectual, spiritual, and moral aspects so that modernization does not eliminate pesantren identity.